The Influence of Economic Motivation, Tax Knowledge, and Academic Support on Students' Career Intention to Become Tax Consultants: Evidence From The Tax Accounting Study Program at Universitas Pamulang - Ngatimin Ngatimin; Danang Choirul Umam; Siti Ratna Sari Dewi (Asosiasi Dosen Muda Indonesia, 2026)
This study investigates the influence of economic motivation, tax knowledge, and academic support on students' career intention to become tax consultants among students of the Tax Accounting Study Program at Universitas Pamulang. A quantitative research design with an associative approach was employed using survey data collected from 99 respondents selected through purposive sampling. Data were analyzed using multiple linear regression with IBM SPSS, following validity, reliability, and classical assumption tests. The findings reveal that economic motivation and tax knowledge have positive and significant effects on students' career intention to become tax consultants, whereas academic support does not significantly influence career intention. Among the independent variables, tax knowledge is identified as the strongest predictor, indicating that professional competence plays a more decisive role than institutional support in shaping students' career choices. Simultaneously, the three independent variables significantly explain students' career intention, with the regression model accounting for 60.9% of the variance. These findings contribute to taxation education by emphasizing the importance of competency development and career-oriented learning in preparing future tax professionals.